Co-designing socio-technical Innovation bundles for women’s empowerment and resilient in Ethiopia - Ketema, Dessalegn Molla; Nchanji, Eileen Bogweh (2023)
CGIAR gender equality Initiative update in the Ethiopian learning lab.